The Analysis of Instagram Ads Strategy, Brand Awareness and its Impact on Purchasing Decision of Wardah Facial Wash (Case Study in the Community of Kelurahan Cikutra) - Nabil, Alma Maulida; Prasetyo, Mohamad Hadi (STIE Ekuitas, 2024)
Introduction/Main Objectives: This study examines the influence of Instagram ads and Brand Awareness on the Purchasing Decision of Wardah Facial Wash Purchasing Decisions. Background Problems: The increasingly stringent market developments in the beauty and skin care motivated this research. Cosmetic company is required to have an accurate strategy in retaining its customers, looking for new potential customers, which of course increases sales volume. Research Methods: The research method used is descriptive and verification methods with a quantitative approach, collecting data by distributing questionnaires to 100 respondents. Statistical analysis instruments used validity test, reliability test, classical assumption test, path analysis, correlation coefficient analysis, and coefficient of determination. Finding/Results: The result is that there is an influence between Instagram ads on purchasing decisions through the Brand Awareness variable as an intervening variable. Consumer Purchase Decision is included in the